Reduced Scan Time in 123I-FP-CIT SPECT Imaging Using a Large-Field Cadmium-Zinc-Telluride Camera. (July 2019) - Bani Sadr, Alexandre; Testart, Nathalie; Tylski, Perrine; Scheiber, Christian
Abstract : Abstract: We evaluated the reproducibility of 123 I-ioflupane ( 123 I-FP-CIT) SPECT with shorter scan times using a CZT camera. One hundred ninety-nine 123 I-FP-CIT SPECT scans obtained with standard scan time (30 minutes) were truncated to provide 24-, 18-, and 15-minute study simulations. Striatal binding ratios were automatically calculated and remained stable for all series. At 15 minutes, only 10 of 398 striata (2.5%) showed statistically significant different striatal binding ratios compared with reference series. These series were reviewed by 2 operators, and a perfect agreement was found for each patient. Therefore, CZT camera allows a 2-fold scan time reduction in 123 I-FP-CIT SPECT.